Implementation of Teacher Competency Policy at SDN 2 Lubuk Seberuk, School of Mover Class II - Septri Yuspita; Nur Ahyani; Muhammad Fahmi (International Journal of Multilingual Education and Applied Linguistics, 2025)
This thesis examines the implementation of the teacher competency policy at SDN 2 Lubuk Seberuk, a second-cohort "Sekolah Penggerak" (Driving School) under Indonesia’s Ministry of Education initiative. The study aims to analyze how policy directives regarding teacher competencies—covering pedagogical, professional, personal, and social aspects—are applied in the school's daily practices. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis involving school principals, teachers, and educational supervisors. The findings indicate that while the policy has provided a clear framework for competency development, its implementation faces challenges such as limited resources, varying teacher readiness, and the need for continuous professional development. Nevertheless, the school shows progress in fostering a collaborative learning environment and integrating innovative teaching methods. The study concludes that effective policy implementation requires strong leadership, sustained support systems, and active stakeholder involvement to enhance teacher performance and student learning outcomes.